2009
DOI: 10.1186/1471-2229-9-124
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds in ectomycorrhizal interaction of lignin modified silver birch

Abstract: BackgroundThe monolignol biosynthetic pathway interconnects with the biosynthesis of other secondary phenolic metabolites, such as cinnamic acid derivatives, flavonoids and condensed tannins. The objective of this study is to evaluate whether genetic modification of the monolignol pathway in silver birch (Betula pendula Roth.) would alter the metabolism of these phenolic compounds and how such alterations, if exist, would affect the ectomycorrhizal symbiosis.ResultsSilver birch lines expressing quaking aspen (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 85 publications
1
9
0
Order By: Relevance
“…The lower concentration (μg mg −1 DW) of lead in inoculated roots, especially those inoculated with the non-tolerant strain, may have resulted from ECM increasing the production and extraction of phenolic compounds (Schützendübel and Polle 2002;Jacob et al 2004) or metallothioneins (Courty et al 2011), which both form complexes with heavy metals. However, effect of mycorrhizae on phenolic compounds has not been fully characterized, and differs among various symbiotic interactions (Sutela et al 2009). Moreover, some phenolic compounds exhibit antimicrobial activities (Münzenberger et al 1995), and may delay the mycorrhization process, possibly observed for non-tolerant strain.…”
Section: Benefits Of Ectomycorrhizal Fungi On Plants Grown In the Prementioning
confidence: 99%
“…The lower concentration (μg mg −1 DW) of lead in inoculated roots, especially those inoculated with the non-tolerant strain, may have resulted from ECM increasing the production and extraction of phenolic compounds (Schützendübel and Polle 2002;Jacob et al 2004) or metallothioneins (Courty et al 2011), which both form complexes with heavy metals. However, effect of mycorrhizae on phenolic compounds has not been fully characterized, and differs among various symbiotic interactions (Sutela et al 2009). Moreover, some phenolic compounds exhibit antimicrobial activities (Münzenberger et al 1995), and may delay the mycorrhization process, possibly observed for non-tolerant strain.…”
Section: Benefits Of Ectomycorrhizal Fungi On Plants Grown In the Prementioning
confidence: 99%
“…The down-regulation of COMT in silver birch led to no change in lignin content, and did not affect the feeding preference of insect herbivores or the interactions with the ectomycorhhizal fungus Paxillas involutus (Tiimonen et al, 2005;Sutela et al, 2009). …”
Section: Caffeic Acid O-methyltransferasementioning
confidence: 99%
“…The few studies to date with lignin-modified GM birch and its ectomycorrhizal fungus Paxillus involutus (Batsch) Fr. have produced only limited evidence of impacts (Seppanen et al, 2007;Sutela et al, 2009;Tiimonen et al, 2008).…”
Section: Possible Impacts Of Altered-lignin Gm Pines On Invertebrate mentioning
confidence: 99%